2008
DOI: 10.1590/s0034-72992008000500005
|View full text |Cite
|
Sign up to set email alerts
|

Teste Dicótico de Dígitos (etapa de escuta direcionada) em crianças com fissura labiopalatina

Abstract: Perdas auditivas condutivas nos primeiros anos de vida podem levar a transtornos do processamento auditivo, de atenção e, conseqüentemente, dificuldades de aprendizado da comunicação. OBJETIVO: Verificar o desempenho de crianças com fissura labiopalatina no teste dicótico de dígitos, etapa de escuta direcionada; e compará-los aos de um grupo sem fissura labiopalatina. MATERIAL E MÉTODO: Fizeram parte deste estudo 52 crianças, de ambos os gêneros, na faixa etária de sete anos a sete anos e 11 meses, que foram d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
(8 reference statements)
0
6
1
5
Order By: Relevance
“…A study (11) intends to check labial palatine fissure children in the Dichotic Listening Test and compare them with a group without labial palatine fissure reports the difference in boys' and girls' performance, in which the girls show lower ratios of right answers than those in the studied control group, in opposition to the present work, which showed no significance between the sexes. Consideration must be taken because the studied stage by the authors (11) was focused on a stage of binaural separation-requiring directed listening, in which the listener pays attention to a sound introduced into an ear, while ignoring the other sound simultaneously introduced into the other ear. This has been referred to as directed auditory attention (23).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…A study (11) intends to check labial palatine fissure children in the Dichotic Listening Test and compare them with a group without labial palatine fissure reports the difference in boys' and girls' performance, in which the girls show lower ratios of right answers than those in the studied control group, in opposition to the present work, which showed no significance between the sexes. Consideration must be taken because the studied stage by the authors (11) was focused on a stage of binaural separation-requiring directed listening, in which the listener pays attention to a sound introduced into an ear, while ignoring the other sound simultaneously introduced into the other ear. This has been referred to as directed auditory attention (23).…”
Section: Discussioncontrasting
confidence: 84%
“…Neurological or sensorial alterations, such as peripheral and/or central auditory alterations, are emphasized on the population having a low weight at birth (1)(2)(3)(4)(5), as well as the presence of craniofacial malformation, such as labial palatine fissure (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The population with a history of otitis media showed worse results in the assessment of the auditory processing in the skills of sound localization, memory for sounds in sequence and auditory integration when compared with the population with no history of otitis media; this population had the worst performances in the auditory closure and figure-ground abilities 23 . Similarly, in another study, a lower performance was found on the figure-ground ability of children with cleft lip and palate through the Dichotic Listening Test compared to children without it 24 .…”
mentioning
confidence: 65%
“…Verificou-se, em relação às dificuldades escolares, maior predomínio das dificuldades no aprendizado da leitura e da escrita, seguido das dificuldades no raciocínio matemático. Estes achados são concordantes com outros estudos que evidenciam a fissura labiopalatina como indicador de risco para distúrbios na aquisição de linguagem oral e escrita (11,15,23) . Quanto ao desempenho escolar, 58% dos professores referem que os alunos com fissura labiopalatina apresentam desempenho na média da classe.…”
Section: Discussionunclassified
“…Os achados dos exames timpanométricos dos alunos com fissura labiopalatina denotaram o histórico positivo de alteração de orelha média em 60% destes. A audição periférica da população com fissura labiopalatina tem sido amplamente estudada, visto a importância da percepção sensorial e das habilidades auditivas para a aprendizagem (10)(11)(12)23) .…”
Section: Discussionunclassified